Interference and Protection in Satellite Laser Communication - Chenzhe LAO; Jianfeng SUN (天地一体化信息网络)
In order to explore the safety protection technologies for various external interferences in satellite laser communication, four interference sources in the satellite laser communication link and their principles were introduced, included atmospheric turbulence, space background noise, weak light interference, and strong laser interference.And numerical models commonly used in theoretical analysis of the first two interferences were provided.Weak light interference and strong laser interference, also known as laser active interference, were artificial interference methods.From the scheme of communication, the impact of these four interference sources on coherent and incoherent communication systems was analyzed, and the current mainstream protection technologies for these four interferences under different systems were provided.The characteristics of various protection technologies were compared from versatility, cost, usability and their main application scenarios in satellite laser communication were explained.